The Molecular Structure of 4-Methyl Benzenesulfonyl Chloride - Rigotti, Guillermo (1986)
The molecular structure of C7H7SO2CI was determined by X-ray diffraction and refined to R = 0.060 and Rw = 0.053 from 1170 unique reflections. The unit cell is triclinic, P1, with Z = 2, a = 8.528(5), b = 8.214(3), c = 6.306(2) A; a = 95.47(3), ß = 104.41(3), y = 93.08(4)°; V = 424.6(3) Å³; u = 6.30 cm⁻¹; δcale = 1.49 Mg. m⁻³; F(000) = 196. The dihedral angle between the benzene ring and the CI-S-C(l) plane [84.3(1)°] is similar to those observed for benzenesulfonyl chlorides where molecular packing results from normal van der Waals interactions [1, 2], The compound has normal bond lengths and angles. Distortion of the benzene ring is in agreement with the predicted σ- and π-effects of substituent groups [3], No significantly short intermolecular distances were found.